2005
DOI: 10.1536/ihj.46.583
|View full text |Cite
|
Sign up to set email alerts
|

A Case-control Pilot Study on n-3 Polyunsaturated Fatty Acid as a Negative Risk Factor for Myocardial Infarction

Abstract: SUMMARYThe relation between n-3 polyunsaturated fatty acid (PUFA) and nonfatal myocardial infarction is still controversial.A multicenter case-control pilot study on n-3 PUFA as a negative risk factor for myocardial infarction was performed in Niigata prefecture. Seventy-three patients with acute myocardial infarction (AMI) and age and gender matched controls (n = 84) were recruited. Serum leptin levels were significantly higher in patients with AMI than the controls (8.1 ± 6.7 ng/mL versus 5.8 ± 3.7 ng/mL, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…[31][32][33] Guallar, et al reported that there was no difference in plasma fish oil levels between patients with myocardial infarction and the control in a prospective nested case-control study (the Physician's Health Study), 31) while Tavani, et al showed in their case-control study that n-3 PUFA was inversely related to nonfatal myocardial infarction. 33) We reported that n-3 PUFA may be negatively related to nonfatal myocardial infarction and the optimal n-6/n-3 PUFA ratio may be lower than 3/1 in a case-control study 9) conducted in Japan where the incidence of myocardial infarction is low and the mean ratio of n-6/n-3 PUFA is about 3/1. Siscovick, et al suggested a possible threshold for n-3 PUFA intake (the equivalent of one fatty fish meal a week) for a marked reduction in cardiac sudden death.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[31][32][33] Guallar, et al reported that there was no difference in plasma fish oil levels between patients with myocardial infarction and the control in a prospective nested case-control study (the Physician's Health Study), 31) while Tavani, et al showed in their case-control study that n-3 PUFA was inversely related to nonfatal myocardial infarction. 33) We reported that n-3 PUFA may be negatively related to nonfatal myocardial infarction and the optimal n-6/n-3 PUFA ratio may be lower than 3/1 in a case-control study 9) conducted in Japan where the incidence of myocardial infarction is low and the mean ratio of n-6/n-3 PUFA is about 3/1. Siscovick, et al suggested a possible threshold for n-3 PUFA intake (the equivalent of one fatty fish meal a week) for a marked reduction in cardiac sudden death.…”
Section: Discussionmentioning
confidence: 96%
“…34) We suggest another higher possible threshold for a reduction in nonfatal myocardial infarction, because the protective effects of n-3 PUFA from nonfatal myocardial infarction are obscure in Western cultures where n-3 PUFA intake is very low, 29,31,32) whereas these effects may be evident in epidemiological studies comparing different (in regard to fish consumption) ethnic groups 35) and the protective effect was observed at very high levels of n-3 PUFA compared to those in Western cultures in our previous study. 9) NA, as well as DHA, is well-known as a major component of brain phospholipids, and has been suggested as a therapeutic supplement for demyelinating diseases by some investigators. 36) However, it is catabolized in peroxisomes as are other very long chain fatty acids, and this process is defective in some demylinating diseases, so, the efficacy of dietary NA therapy has been questioned by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is there a potential for this nutritional research to be translated into effective preventive medicine applications for the general public? ALA ingestion can impact primary cardiovascular endpoints like morbidity and mortality due to a myocardial infarction in large sample populations over multi-year follow-up studies [22][23][24][25][26][27][28][29][30]. The National Heart, Lung, and Blood Institute Family Heart Study (NHLBI-FHS) showed that an ALA rich diet is associated with a lower prevalence of calcified atherosclerotic plaque in coronary arteries [26].…”
Section: The Causes Of Cardiovascular Diseasementioning
confidence: 99%
“…Baylin et al [24] reported an inverse relation between ALA in adipose tissue and non-fatal acute myocardial infarction. Oda et al [25] demonstrated that serum levels of ALA, EPA, DHA, and total n−3 polyunsaturated fatty acids (PUFA) were significantly lower in patients with acute myocardial infarction in comparison to the control group. The Health Professionals Follow-up Study investigated 43,757 health professionals aged 40 to 75 years of age who were free of diagnosed cardiovascular disease or diabetes.…”
Section: The Causes Of Cardiovascular Diseasementioning
confidence: 99%